A STUDY REGARDING USE OF LIBRARY INFORMATION RESOURCES BY THE STUDENTS OF TIKA RAM COLLEGE OF EDUCATION, SONEPAT. (International Journal of Food and Nutritional Sciences, 2022)
"Information literacy is a way of learning through engaging with information. Information literacy includes library research skills' and 'IT literacy' but it is broader than these. Information literacy is not just about finding and presenting information, it is about higher order analysis, synthesis, critical thinking and problem solving. It involves seeking and using information for independent learning, lifelong learning, participative citizenship and social responsibility." This Research paper throw light on the use of Library Resources by the students of Tika Ram College of Education, Sonepat. For their information what type of resources they prefer. The paper try to analyze what kind of methods and resources must be used in information literacy instruction provided by an academic library.